2006
DOI: 10.1534/genetics.106.059659
|View full text |Cite
|
Sign up to set email alerts
|

A Polymorphism in the 5′-Untranslated Region of the Porcine Cholecystokinin Type A Receptor Gene Affects Feed Intake and Growth

Abstract: The location and utilization of quantitative trait loci (QTL) and candidate genes with significant effects on economically important traits are becoming increasingly important in livestock breeding programs. The porcine cholecystokinin type A receptor (CCKAR) is a candidate gene for performance traits, due to its known role in the physiological control of feed intake, satiety, and obesity. We investigated the association of CCKAR polymorphisms with feeding, growth, and efficiency traits in an F 2 population de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…One hypothesis that might explain the observed association between CCKAR genotypes and growth traits is that g. 420 A represses the transcriptional activity of the CCKAR gene, leading to a reduced satiety effect and increased appetite and growth. In pigs, Houston et al (2006) reported that a low-affinity YY1 binding site in the 5′ -UTR of the CCKAR gene might be related to high growth performance. Meanwhile, our data showed that a high affinity YY1 binding site in the 5′ -UTR of the CCKAR gene might be related to high growth performance in chickens.…”
Section: Resultsmentioning
confidence: 99%
“…One hypothesis that might explain the observed association between CCKAR genotypes and growth traits is that g. 420 A represses the transcriptional activity of the CCKAR gene, leading to a reduced satiety effect and increased appetite and growth. In pigs, Houston et al (2006) reported that a low-affinity YY1 binding site in the 5′ -UTR of the CCKAR gene might be related to high growth performance. Meanwhile, our data showed that a high affinity YY1 binding site in the 5′ -UTR of the CCKAR gene might be related to high growth performance in chickens.…”
Section: Resultsmentioning
confidence: 99%
“…Polymorphisms, including one in a YY1 transcription binding site in the CCKAR promoter, were associated with growth in pigs (28, 29). It was suggested that snp.13.786.12116.S.3 might effect this transcription binding site in chickens, but no evidence was presented (54).…”
Section: Discussionmentioning
confidence: 99%
“…A major focus for the discovery of polymorphisms in production animals has been to identify those associated with traits that are considered to be economically important such as lean muscle accretion, feed efficiency, and growth (Franco et al, 2005;de Oliveira Peixoto et al, 2006;Houston et al, 2006;Verner et al, 2007;Nie et al, 2008). Far fewer studies have identified polymorphisms associated with overall animal health, specifically as it relates to bone health.…”
Section: Discussionmentioning
confidence: 99%